Phosphorylation of 2-(3-Methyl-1,3-diazabuten-1-yl)-3-Ethoxycarbonylthiophenes with Phosphorus(III) Halides - Pinchuk, Alexander; Kovaleva, Svetlana; Ivonin, S.; Merkulov, A.; Kudrya, Tamara; Chaikovskaya, Alexandra; Tolmachev, Andrei (My University, 2001)
Method of selective C5-phosphorylation of derivatives of 2-amino-3-ethoxycarbonylthiophene containing N,N-dimethylformamidine gpoup at the 2nd position of the heterocycle was affered. Derivatives of 2-(3-methyl-1,3-diazabuten-1-yl)-3-ethoxycarbonylthiophene were studied in reactions with Phosphorus(III) Halides. Based on C5-phosphorylated N,N-dimethylamino-N’-(2-thienyl)formamidines the methods for synthesis of new and biologically promising C-phosphorylated derivatives of 2-amino-3-thiophenecarboxylic acids and thieno[2,3-b]pyrimidones were elaborated. Запропоновано метод селективного С5-фосфорилювання галогенідами фосфору (III) похідних 2-аміно-3-етиксикарбонілтіофену, що містять N,N-диметилформамідиновий залишок біля С2-атому гетероциклу. На основі С5-фосфорильованих N,N-диметиламіно-N’-(2-тієніл)формамідинів розроблені методи синтезу невідомих раніше та перспективних в біологічному плані С-фосфорильованих похідних 2-аміно-3-тіофенкарбонових кислот та тієно[2,3-b]піримідонів.
Keywords: тіофен; амінотіофен; амідин; тієнопіримідон; тієнілфосфін; фосфорилювання; thiophene; aminothiophene; amidine; thienopyrimidon; thienylphosphine; phosphorylation; кафедра харчової хімії